Spontaneous labor patterns among women attempting vaginal birth after cesarean delivery. (12th December 2022) - Shalev-Ram, Hila; Miller, Netanella; David, Liron; Issakov, Gal; Weinberger, Hila; Biron-Shental, Tal
Abstract: Objective: This study evaluated spontaneous labor patterns among women achieving a vaginal birth after cesarean (VBAC), without a previous vaginal delivery in relation to nulliparous women. Methods: This historical cohort study included 422 women attempting VBAC and 150 nulliparas. We examined time intervals for each centimeter of cervical dilation and compared labor progression in 321 women who achieved spontaneous VBAC and 147 nulliparous women achieving a spontaneous vaginal delivery. Epidural anesthesia use, delivery mode, cord arterial pH and 5-minute Apgar score were also compared. Findings: Women in the VBAC group compared to nulliparous women had similar durations of first (4–10 cm: 4:22 (00:54–13:10) h vs. 4:47 (1:10–15:10) h, p = .61), second (1:07 (8:00–3:21), vs. 1:34 (10:00–3:40), p = .124) and third stages of labor (10:00 (2:00–22:00) vs. 08:00 (3:24–22:12), p = .788). When comparing women who had epidural analgesia to those who did not, no differences were found between the groups regarding durations of first and second stages of labor. Interestingly, among parturients without epidural anesthesia only, the VBAC group had shorter second stage compared to the nulliparous (00:19 (0:04–1:59) vs. 00:47 (0:08–2:09), p = .023). Conclusion: Labor patterns among women achieving spontaneous VBAC are similar to those of nulliparous women with spontaneous vaginal deliveries.